Reinsertion of distal biceps ruptures with a single anterior approach: analysis of 14 cases using tension-slide technique and interference screw - Micheloni, Gian Mario; Tarallo, Luigi; Porcellini, Giuseppe; Novi, Michele; Catani, Fabio (Acta Biomedica Atenei Parmensis, 2020)
Background: Several techniques of surgical repair of biceps tendon ruptures are described in literature.Cortical button repair have shown minimal loss of elbow flexion, supination and strength. In this retrospectivestudy we report the outcomes in terms of elbow function and complications of tension-slide technique andinterference screw. Matherials and methods: 14 patients with complete distal biceps tendon rupture were included in the retrospective study and treated with the same tension-slide technique (BicepsButton® - Arthrex, Inc, Naples, Florida) evaluating the clinical and functional outcomes and the complication rate with a follow-upaverage of 18 months. Results: The flexion recovered compare to the healthy contralateral was 96% (min 115° -max 135°; average 128°), the extension was 97% (min: -2° - max 15°; average 4°), the supination was 90% (min20° - max 90°; average 75°), the pronation was 95% (min 15° - max 90°; average 76°). The mean Disabilitiesof Arm, Shoulder and Hand (DASH) score was 8.1 ± 10.5 and Mayo Elbow Performance Score overall(MEPS) score was 97.6 ± 8.2. Two patients had LABCN paresthesia, one case, treated 2 months after injury,had posterior interosseus nerve palsy. One patient had heterotopic ossification at the radiological examinationwithout consequences for the clinical performances. No case of non-traumatic tendon re-rupture and no caseof ROM deficiency > 20%. In all case the cortical button remains well positioned and no case of osteolysis werereported. Conclusions: Distal biceps tendon repair with BicepsButton® system seems to be a safe, relyable andreproducible technique providing excellent clinical, functional and radiological outcomes. Comparing with othertechniques the BicepsButton® system has the advantages of the single approach procedures, the reduction ofsurgical time and risk of heterotopic ossifications. (www.actabiomedica.it)